Desirable but not feasible: Measures and interventions to promote early childhood health and development in marginalized Roma communities in Slovakia - Filakovska Bobakova, Daniela; Chovan, Shoshana; Bosakova, Lucia; Koky, Richard; de Kroon, Marlou L. A.; Dankulincova Veselska, Zuzana (Frontiers in Public Health, 2022)
Roma are the largest and most disadvantaged ethnic minority in Europe often facing generational poverty, and limited access to education, employment, housing, and various types of services. Despite many international and national initiatives, children from marginalized Roma communities face multiple risks and are being disadvantaged as early as from conception onward. We, therefore, aimed to identify measures and/or interventions targeting equity in early childhood health and development in marginalized Roma communities which implementation is considered to be urgent but not feasible. We used a group concept mapping approach—a participatory mixed research method—and involved 40 experts and professionals from research, policy and practice. From 90 measures and interventions proposed to achieve early childhood equity for children from marginalized Roma communities, 23 measures were identified as urgent but not feasible. These concerned particularly measures and interventions targeting living conditions (including access to income, access to housing, and basic infrastructure for families) and public resources for instrumental support (covering mainly topics related to financial and institutional frameworks). Our results reflect the most pressing issues in the area of equality, inclusion and participation of Roma and expose barriers to implementation which are likely to arise from public and political discourses perpetrating a negative image of Roma, constructing them as less deserving. Measures to overcome persistent prejudices against Roma need to be implemented along with the measures targeting equity in early childhood health and development.